1984
DOI: 10.1128/jb.158.3.1161-1162.1984
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of isotope from specifically labeled glucose into alginates of Pseudomonas aeruginosa and Azotobacter vinelandii

Abstract: The incorporation of isotope from [6-14C]glucose into alginate by both Pseudomonas aeruginosa and Azotobacter vinelandii was 10-fold greater than that from either [1-14C]- or [2-14C]glucose, indicating preferential utilization of the bottom half of the glucose molecule for alginate synthesis. These data strongly suggest that the Entner - Doudoroff pathway plays a major role in alginate synthesis in both P. aeruginosa and A. vinelandii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Several Gram-negative, aerobic microorganisms that are related to the pseudomonads appear to utilize the Entner-Doudoroff pathway in the cyclic mode. It has been shown that incorporation of labelled glucose into alginate by Azotobacter vinelandii involves recycling of triose phosphates [60,61]. In Alcaligenes eutrophus, phosphoglycerate mutase mutants lose the ability to grow on succinate, but are still able to grow on fructose, a pattern similar to that observed for Pseudomonas mutants of the triose phosphate pathway [62].…”
Section: 'Cycfic' Pathwaymentioning
confidence: 73%
“…Several Gram-negative, aerobic microorganisms that are related to the pseudomonads appear to utilize the Entner-Doudoroff pathway in the cyclic mode. It has been shown that incorporation of labelled glucose into alginate by Azotobacter vinelandii involves recycling of triose phosphates [60,61]. In Alcaligenes eutrophus, phosphoglycerate mutase mutants lose the ability to grow on succinate, but are still able to grow on fructose, a pattern similar to that observed for Pseudomonas mutants of the triose phosphate pathway [62].…”
Section: 'Cycfic' Pathwaymentioning
confidence: 73%
“…During atginate synthesis. GDP-D-mannose is formed following enzymatic conversion starting with fnjctose-6-phosphate, derived from the Entner-Doudoroff pathway (Lynn and Sokatch. 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis starts with the entry of six carbon substrates into the Entner–Doudoroff pathway, resulting in pyruvate, which is channelled towards the tricarboxylic acid cycle. Subsequently, oxaloacetate is converted to fructose‐6‐phosphate via gluconeogenesis (Lynn and Sokatch, ; Narbad et al ., ). Three well‐characterized enzymes, AlgA, AlgC and AlgD, catalyse the four next biosynthesis steps to convert fructose‐6‐phosphate to GDP‐mannuronic acid and these enzymes have been.…”
Section: Microbial Biosynthesis Of Alginatementioning
confidence: 99%